Monte Carlo MCNP-based simulation and radiation measurement of Yttrium-90 bremsstrahlung produced from radiation shielding apparatus - C. Onnomdee (2019)
© Published under licence by IOP Publishing Ltd. Yttrium-90 (90Y) has been widely used in therapeutic nuclear medicine including in the selective internal radiation therapy with 90Y-microsphere. In the procedure 90Y source is protected within the radiation shielding apparatus made of perspex. However, bremsstrahlung radiation may be generated when 90Y interacts with matter. The aim of this study was to evaluate bremsstrahlung radiation produced from radiation shielding apparatus using a scintillation detector and Monte Carlo simulation. The 90Y source in glass vial was placed in the radiation shielding apparatus. Bremsstrahlung measurement and spectrum were performed and recorded using thallium-doped sodium iodide (NaI(Tl)) scintillation detector. Counting time and distance between the detector and apparatus were varied to obtain the optimal condition for bremsstrahlung measurement. Monte Carlo N-Particle (MCNP) 5 was used to simulate bremsstrahlung radiation with the same geometry used in the measurement. For experimental measurement results, the optimal distance and counting time were 10 cm and 120 s, respectively. Although the result of bremsstrahlung spectrum from the detector and simulation exhibited similar trend, markedly greater count rate was observed in simulations than in detector measurements. In conclusion, 90Y bremsstrahlung can be produced from radiation protection apparatus and this can be evaluated by either measurement or simulation.